DEVELOPMENT OF THE BOOK RESEARCH METHODOLOGY ASSISTED MIND MAP FOR PGSD STUDENTS UNIVERSITAS NEGERI SEMARANG - Florentina Widihastrini; Trimurtini; Sri Susilaningsih; Kurniana Bektiningsih; Umar Samadhy (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
PGSD (elementary school teacher Education)'s research skills affect the quality of the resulting thesis, which also affects the length of student thesis completion. The purpose of this research is to develop the book of research methodology in PGSD, with the need for examples of research topics in elementary school with a mind map to make the mindset more and more skilled and lead students in research. This development research uses the model ADDIE: Analysis, Design, Development, Implementation, Evaluation. Analysis of the data conducted, i.e. analysis of teaching materials feasibility, analysis of student responses to teaching materials, analysis of increased learning outcomes. The results of a need analysis showed 94.56% of students needed a complete and systematic learning resource innovation and equipped with a mind map as a guideline of thought flow. The content of the teaching book has been designed according to curriculum needs and need analysis results. The Draft I tested validity by material experts got a score of 87.5% (very decent) and by linguist got a score of 96.8% (very decent). Advice from material experts and linguists was made a material to revise the teaching book into Draft II, which was then tested to be limited to seeing the aspect of readability. Limited test results show student responses to the study methodology teaching book in excellent category (85.71%). Student learning results have increased and the results of N-gain test show the increase of the low category (0.26). The conclusion is the book of Research Methodology assisted mind map is valid and well worth using.